Stress-Optical Effect Analysis On Silicon-On-Insulator Planar Waveguide - A. Aziz, N. Nadia; Haroon, Hazura; Abdul Razak, Hanim; Mohd Zain, Anis Suhaila; Othman, Syariffah; Salehuddin, Fauziyah (Penerbit Universiti, UTeM, 2017)
Stress application can be used to modify the optical properties of a device. The stress-optic effect has been experimentally measured in strained silicon, making it a promising candidate material for realizing active photonic devices, such as optical modulators and switches. In this paper, we investigated the stress-optic effect induced by applied strain gradient in the silicon optical waveguides. The relation between stress-optic effect, strain, birefringence and the change in the optical properties is investigated. The structure of nanometer waveguide is analyzed by using the Multiphysics modeling to show the effects of stress analysis. The stress effects are then evaluated by the Structural Mechanics modules.